AN ANALYSIS OF THE SPEAKING MATERIALS IN “ENGLISH ALIVE 2” TEXTBOOK FOR THE ELEVENTH GRADERS OF SENIOR HIGH SCHOOL (RETAIN, 2013)
The objectives of the study are to describe the presentation of speaking materials in “English Alive 2” textbook for the eleventh graders of Senior High School based on the criteria of a good textbook proposed by Savignon, to describe the relevancy of the speaking materials in “English Alive 2” published by Yudhistira for the eleventh graders of Senior High School to the 2006 English standard competence and to describe the sequence of speaking materials in “English Alive 2” published by Yudhistira for the eleventh graders of Senior High School to the 2006 English standard competence. Based on the analysis,the researcher found that the presentation of the textbook was arranged to meet the criteria proposed by Savignon. The researcher also found that the relevancy of the speaking material was quite in line to the 2006 English Standard Competence, but there were some competence that was not in line to the 2006 English Standard Competence. The reasons were the textbook did not present the material in the speaking ability. Another reason was the textbook did not provide the material for the certain competence. For the sequence of the speaking material in the textbook, the researcher found that the sequences are not in line compared to the 2006 English Standard Competence. Keywords:analysis, textbook, eleventh graders, speaking material.